When the courts have to rule on government decisions - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2019)
In a commentary, SMU Associate Professor of Law Eugene Tan cited examples in United Kingdom and Singapore as he discussed the legal limits of legal power and the constitutional role of the courts. He pointed out that the message from the courts for both cases is that “judicial deference notwithstanding, the judiciary will not shy away from limiting the boundaries of executive discretion where it is necessary to do so such as when a fundamental constitutional principle or fundamental liberties are at stake”.